2018
DOI: 10.1055/a-0581-9119
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic retrograde appendicitis techniques for the treatment of patients with acute appendicitis

Abstract: ERAT provide a new alternative therapeutic method for patients with acute appendicitis, particularly for certain patients who are unwilling to undergo an appendectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Finally, as first preliminary data on endoscopic treatment of acute appendicitis is published, maybe conservative treatment will be further improved by combining antibiotic treatment with endoscopic drainage of the appendiceal lumen by a stent [40,41]. …”
Section: Discussionmentioning
confidence: 99%
“…Finally, as first preliminary data on endoscopic treatment of acute appendicitis is published, maybe conservative treatment will be further improved by combining antibiotic treatment with endoscopic drainage of the appendiceal lumen by a stent [40,41]. …”
Section: Discussionmentioning
confidence: 99%
“…There is no gold standard for the preoperative diagnosis of appendicitis and the clinical manifestations (e.g., Alvarado score) are still used for the diagnosis. In recent years, a retrospective study and analysis showed that using endoscopy with appendiceal cavity imaging to observe the internal orifice and surrounding mucosa of the appendix along with data obtained by X-ray or ultrasound can accurately diagnose acute appendicitis [2][3]11]. Even with the progress of endoscopic technology, there is still little evidence that appendiceal cavity imaging can accurately exclude appendix disease.…”
Section: Discussionmentioning
confidence: 99%
“…They underwent ultrasound followed by colonoscopy with digital single-operator cholangioscopeassisted ERAT upon confirmation. 2 Follow-up was by telephone call, which all patients answered. ▶…”
Section: Patients N 14mentioning
confidence: 99%
See 1 more Smart Citation
“…Small studies have shown that it is associated with high rates of clinical efficacy (96%-100%). 15 , 16 , 17 …”
mentioning
confidence: 99%